Architectural and Technological Progress in Modern Mobile Computing - V. Basil Hans (International Journal of Mobile Computing Technology, 2026)
Over the last decade, mobile technologies have experienced rapid and transformative growth, reshaping the way individuals interact with the world and redefining multiple sectors, including healthcare, education, communication, and commerce. Continuous improvements in mobile hardware, such as faster processors, enhanced sensors, and longer-lasting batteries, have significantly improved device performance and usability. At the same time, the widespread development of mobile applications has expanded the functional scope of smartphones, enabling personalized, on-demand services across diverse domains. The deployment of advanced wireless communication infrastructures, particularly high-speed networks such as 5G, has further accelerated data transmission, reduced latency, and supported real-time applications. In parallel, the integration of emerging technologies—including artificial intelligence, cloud computing, and the Internet of Things—has strengthened mobile platforms, allowing smarter automation, data-driven decision-making, and seamless connectivity between devices. This paper also explores key design trends that emphasize user experience, accessibility, and energy efficiency, along with growing security mechanisms aimed at protecting sensitive information. Additionally, it examines the broader economic and social implications of mobile technology adoption, highlighting challenges related to data privacy, cybersecurity risks, and the digital divide. By analyzing current trends and anticipated future developments, this study provides a comprehensive overview of how mobile technologies continue to drive innovation and play a central role in shaping the global digital landscape.
Keywords: 5G networks; artificial intelligence; digital transformation; mobile applications; mobile technologies